TERMINAL CASES LUNG AND HEART RESUSCITATION TRANSFER PRINCIPLES - Asfandiyorov Javodbek Mirzaali o’g’li; Xushvaqtov Ilyos Shodiqul o’g’li; Nazarovov Asadjon Fozil o’g’li; Hasanova Sevinch Ulug‘bek qizi; Tijiddinov Davronbek Ulug‘bek o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides detailed information on providing resuscitation care to patients with heart and lung diseases. In addition, brief information about resuscitation was given.